THE EFFECT OF H3BO3 AND B2O3 ADDITION ON NICKEL MATTE FORMATION FROM SAPROLITIC NICKEL ORE AT 1100ÂºC-1350ÂºC - Miertha Nadya Salsabilla, Ayu
Saprolite nickel laterite ores are generally processed to produce ferronickel containing 10-30% Ni and 70-90% Fe, which can be used for manufacturing of stainless steel and other alloys. Commonly used technology for processing laterite nickel ore through pyrometallurgical routes is the Rotary Kiln-Electric Furnace (RK-EF). The RK-EF process requires a lot of energy because it operates at high temperatures of 1400ºC–1700ºC. In this research, the effect of temperature and the addition of H3BO3 and B2O3 on the reduction process of laterite nickel ore using coal as a reducing agent were studied to see the formation of nickel in metal. Saprolite nickel ore, coal, Na2SO4, H3BO3, and B2O3 agglomerate to form six types of briquettes, namely briquettes A (10% coal addition, 20% Na2SO4), briquettes B (10% coal addition, 20% Na2SO4, 5% H3BO3), briquettes C (addition of 10% coal, 10% Na2SO4, 10% H3BO3), briquettes D (addition of 10% coal, 10% H3BO3), briquettes E (addition of 10% coal, 5.63% B2O3), and briquettes F (addition of 10% coal, 10% Na2SO4, 5.63% B2O3) The reduction process was carried out at temperatures of 1100ºC, 1200ºC, 1300ºC, and 1350ºC using a muffle furnace for 60 minutes. The reduced briquettes were then prepared to be observed using an optical microscope. The results of observations using an optical microscope. The experimental results obtained in the form of data on changes in sample weight after being reduced and the appearance of the microstructure using an optical microscope. The weight change data then compared with the Factsage simulation results for analysis. From the experiment, it was concluded that increasing the temperature could increase the weight of the mate produced. The addition of H3BO3 can lower the melting temperature of the slag so that the metal and slag are easier to separate. B2O3 is proven more effective as an additive.